The Immune Regulatory Functions of CD226 and Its Implications in Immune-Mediated Diseases - Keyan Liu; Yuanzhen Liu; Huabao Xiong; Zhaochen Ning (Biomolecules, 2025)
CD226, a member of the immunoglobulin superfamily, serves as a critical regulator in various immunological processes. CD226 is expressed across immune and non-immune cells, with predominant expression being observed in natural killer (NK) cells and T cells. By engaging ligands CD155 and CD112, it orchestrates diverse signaling pathways that modulate T cell differentiation and effector functions while enhancing NK cell activation and cytotoxicity. Genetic polymorphisms and the dysregulated expression of CD226 are closely associated with susceptibility to autoimmune diseases, infectious diseases, allergic diseases, and cancer progression. Growing evidence highlight CD226’s emerging promise as a therapeutic target for immune-mediated diseases. The present work aims to review the current understanding of CD226’s role in immune responses and to comprehensively outline its multifaceted involvement in different immunological diseases, providing insights for future research to advance our mechanistic understanding of its roles in disease pathogenesis.